A velhice ativa entre idosos longevos - Markarian, Fabiana de Jesus Paulo (2016)
This dissertation discusses issues related to active longevity, retirement, to free time and the possibilities concerning the elderly leisure. For the survey data were interviewed sixteen elderly, eight women and eight men, retirees or pensioners, who explained their experiences and what they think about the work, longevity, retirement and the possibilities and meanings to stop working, beyond their anxieties and insecurities. It found that some of them have jobs and perform their daily activities. We understand that the elderly do not want to become idle, they understand the work as something pleasant and feel productive working. It discussed the relationship of free time after retirement, how to use it in the best possible way for the old guy can take it. Public spaces were highlighted the importance of the elderly to enter into a specific social context for the coexistence of leisure. Also highlighted are the chances that the elderly have to use public spaces for leisure and for your free time. Was addressed in this dissertation, the issue of public policies for the elderly, in addition to the appointment of some social programs developed in São Paulo and other cities